Expression Of NLRP3 Gene And ProInflammatory Cytokines (IL-1β And IL-18),Levels In Paclitaxel-Induced PeripheralNeuropathy Of Iraqi Breast Cancer Patients (The Review of Diabetic Studies, 2025)
Breast cancer patients undergoing paclitaxel (Taxol) chemotherapy frequently develop paclitaxel-induced a peripheral neuropathy (PIPN), a toxicity that can be considered dose-limiting that significantly impacts quality of life. While the molecular mechanisms remain incompletely understood, emerging evidence suggests that NLRP3 inflammasome activation may play key roles in PIPN pathogenesis.Objective: This study explored the connection between NLRP3 inflammasome activation, pro-inflammatory cytokine levels, and the emergence of PIPN in Iraqi patients with breast cancer (BC) receiving Taxol chemotherapy.Methods: Blood sample draw done and distributed into two tubes: Trizol containing tube for evaluation the gene expression of NLRP3 gene by qRT-PCR and gel tube for measurement of interleukin levelResults: We observed significant molecular changes associated with neurotoxicity. IL-1β levels nearly doubled from 9.43±1.33 pg/mL at baseline to 17.66±3.62 pg/mL post-treatment (p